2011
DOI: 10.1002/aur.194
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorders are associated with an elevated autoantibody response to tissue transglutaminase‐2

Abstract: We report that a significant number of autistic children have serum levels of IgA antibodies above normal to the enzyme tissue transglutaminase II (TG2), and that expression of these antibodies to TG2 is linked to the (HLA)-DR3, DQ2 and DR7, DQ2 haplotypes. TG2 is expressed in the brain, where it has been shown to be important in cell adhesion and synaptic stabilization. Thus, these children appear to constitute a subpopulation of autistic children who fall within the autism disease spectrum, and for whom auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
(56 reference statements)
1
16
1
Order By: Relevance
“…An increase in autoantibody reactivity has been reported against other brain proteins in ASD including nerve growth factor [53], brain endothelium [54], cerebellar proteins [40], and serotonin 5-HT receptors [55] and transglutaminase-2, a protein important in synaptic stabilization [39]. Croonenberghs et al [56] noted a significant increase in gamma globulin especially of the IgG2 and IgG4 subclasses in children with autism over a control population.…”
Section: Immune Abnormalities In Autismmentioning
confidence: 99%
“…An increase in autoantibody reactivity has been reported against other brain proteins in ASD including nerve growth factor [53], brain endothelium [54], cerebellar proteins [40], and serotonin 5-HT receptors [55] and transglutaminase-2, a protein important in synaptic stabilization [39]. Croonenberghs et al [56] noted a significant increase in gamma globulin especially of the IgG2 and IgG4 subclasses in children with autism over a control population.…”
Section: Immune Abnormalities In Autismmentioning
confidence: 99%
“…These last three papers, published by our research group, have all described typical HLA Class I and Class II HLA antigen-presenting alleles which involve different protein binding sites (T-cell receptor) outside the KIR binding sites. Additional immune associations include imbalances in antibody levels (Croonenberghs et al, 2002; Heuer et al, 2008; Enstrom et al, 2009b), an increase in autoantibodies to neural tissue (Cabanlit et al, 2007; Wills et al, 2009; Rosenspire et al, 2011), altered cytokine levels (Molloy et al, 2006; Ashwood et al, 2011), changes in lymphocyte subsets (Furlano et al, 2001), a family history of autoimmune diseases (Atladóttir et al, 2009), and reduced natural killer (NK) cell activity (Warren et al, 1987; Enstrom et al, 2009a). …”
Section: Introductionmentioning
confidence: 99%
“…By examining total serum proteins and serum concentrations of antibodies, Croonenberghs et al (2002) found that children with autism had significantly increased concentrations of albumin and gamma globulin as well as significantly increased levels of IgG subclasses IgG2 and IgG4. Autoantibodies have been detected against several brain proteins including myelin basic protein (Jyonouchi et al, 2001), neuron-axon filament protein and glial fibrillary acidic protein (Singh et al, 1997), nerve growth factor (Bashina et al, 1997), cell nuclei (Stubbs, 1988), brain endothelium (Connolly et al, 1999), Purkinje cells of the cerebellum (Zimmerman et al, 1993), cerebellar proteins (Goines et al, 2011), serotonin 5-HT receptors (Todd & Ciaranello, 1985), and most recently to tissue transglutaminase-2 which is present in the brain and involved in cell adhesion and synaptic stabilization (Rosenspire et al, 2011). Although autoantibodies have been detected against several proteins important in neuronal function, there is no evidence of pathological brain lesions in autism.…”
Section: Humoral Adaptive Systemmentioning
confidence: 99%
“…The AH 8.1 (A1, C7, B8, C4A null allele, DR3, DQ2) also referred to as COX has been entirely sequenced providing information on all of the genes in this haplotype. The AH 44.1 has the DR4 allele that has been associated with RA and the DR3 DQ2 portion of the AH 8.1 is associated with autoantibodies to tissue transglutiminase-2 as is seen in celiac disease (Rosenspire et al, 2011). The C4 null alleles in these two ancestral haplotypes associate with several autoimmune diseases like SLE.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation